Composite photocatalytic material for air purification and preparation method thereof

By loading the phosphomolybdate PMA material in the pores of MIL-125, PMA@MIL-125 composite photocatalytic material is formed, which solves the problem of limited photocatalytic performance of MIL-125, and efficient adsorption and photocatalytic degradation of oxygen-containing VOCs are achieved.

CN119793535APending Publication Date: 2025-04-11SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411806945.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

MIL-125 has problems with low number of photogenerated carriers and high recombination rate under photoexcitation, which seriously limits its photocatalytic performance.

Method used

By loading the PMA material of phosphomolybdate into the pores of MIL-125, PMA@MIL-125 composite photocatalytic material is formed, and the photocatalytic performance is improved by utilizing the high specific surface area of ​​MIL-125 and the electronic storage capacity of PMA.

Benefits of technology

The adsorption capacity and photocatalytic degradation efficiency of the photocatalyst on oxygen-containing VOCs are improved, the recombination rate of photogenerated carriers is reduced, and the number of photogenerated carriers is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793535A_ABST
    Figure CN119793535A_ABST
Patent Text Reader

Abstract

The invention relates to a composite photocatalytic material for air purification and a preparation method thereof. The composite photocatalytic material for air purification comprises an MIL-125MOF material with a high specific surface area and a phosphomolybdic acid (PMA) material which is packaged and loaded in a pore channel of the MIL-125MOF material, wherein the total mass of the composite photocatalytic material for air purification is 100%, the mass ratio of the PMA material is 30-50%, and the mass ratio of the MIL-125 MOF material is 50-70%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of air purification catalyst preparation, and specifically relates to a composite photocatalytic material for air purification and a preparation method thereof. Background Art

[0002] Oxygenated volatile organic compounds (VOCs) are the main organic matter causing air pollution. They are highly volatile and toxic. Long-term exposure to high concentrations of oxygenated VOCs can cause various health problems to the human body, such as headaches, anesthesia, dizziness and nausea. Among the many oxygenated VOCs treatment technologies, photocatalytic oxidation has attracted widespread attention in the field of removing low-flow oxygenated VOCs due to its advantages such as environmental protection, high efficiency and low cost. Among them, the selection and regulation of photocatalysts are the key to efficient photocatalytic degradation of oxygenated VOCs.

[0003] MIL-125 is a titanium-based metal-organic framework (MOF) constructed from Ti8O8(OH)4 metal clusters and organic ligands. Compared with some typical photocatalysts (such as metal oxides, metal sulfides, bismuth-based halogenated oxides and g-C3N4, etc.), MIL-125 has a large specific surface area and abundant reaction sites, and its surface structure is easy to control, which shows great potential in the field of photocatalytic oxidation of VOCs. On the one hand, the rich and uniform pore structure in MIL-125 is conducive to the capture of oxygen-containing VOCs molecules; on the other hand, the presence of tetravalent titanium ions makes MIL-125 have good photocatalytic potential. However, under light excitation, MIL-125 has the problems of low number of photogenerated carriers and high recombination rate, which seriously limits its photocatalytic performance. Summary of the invention

[0004] In view of the above technical problems, the purpose of the present invention is to provide a novel, efficient and practical composite photocatalytic material for degrading oxygen-containing VOCs for air purification. The photocatalyst not only has a high efficiency adsorption capacity for oxygen-containing VOCs, but also exhibits excellent photocatalytic properties.

[0005] In a first aspect, the present invention provides a composite photocatalytic material for air purification, the composite photocatalytic material for air purification comprising: a MIL-125MOF material with a high specific surface area, and a phosphomolybdic acid PMA material encapsulated and loaded in the pores of the MIL-125MOF material; Wherein, taking the total mass of the composite photocatalytic material for air purification as 100%, the mass of the PMA material accounts for 30-50%, and the mass of the MIL-125MOF material accounts for 50-70%.

[0006] Preferably, the average pore size of the MIL-125MOF material is 1-5 nm.

[0007] Preferably, the particle size of the composite photocatalytic material for air purification is in the range of 400-1000 nm.

[0008] Preferably, the specific surface area of ​​the composite photocatalytic material for air purification is 800-1500m 2 / g.

[0009] In a second aspect, the present invention provides a method for preparing the composite photocatalytic material for air purification, the preparation method comprising the following steps: (1) dissolving an organic ligand in a first solvent, adding a metallic titanium source to obtain a mixed solution, and subjecting the solution to high-temperature heating reaction to obtain the MIL-125MOF material; (2) The PMA material and the MIL-125MOF material are stirred and immersed in a second solvent to obtain the composite photocatalytic material for air purification.

[0010] Preferably, in step (1), the organic ligand comprises at least one of terephthalic acid, 2-aminoterephthalic acid, 2-hydroxyterephthalic acid, 2-nitroterephthalic acid, 2,5-diaminoterephthalic acid, 2,5-dihydroxyterephthalic acid, tetrafluoroterephthalic acid, isophthalic acid, phthalic acid, trimesic acid, trimellitic acid, biphenyl trimesic acid, 2,5-dicarboxypyridine, biphenyl dicarboxylic acid, and bipyridine dicarboxylic acid; The metal titanium source includes at least one of tetrabutyl titanate, titanium isobutoxide, titanium tetraisopropoxide, tetraethyl titanate, n-propyl titanate, tetrahydrofuran titanium chloride, isopropyl titanate triisostearate, triisopropoxy titanium chloride, and titanium tert-butoxide.

[0011] Preferably, in step (1), the molar ratio of the metallic titanium source to the organic ligand is (0.2-2):1, preferably (0.5-0.8):1.

[0012] Preferably, in step (1), the temperature of the high temperature heating reaction is 120-180°C, preferably 140-170°C; the time of the high temperature heating reaction is 12-48 hours, preferably 24-36 hours.

[0013] Preferably, in step (2), the second solvent is a medium polar solvent; preferably at least one of methanol, ethanol, acetonitrile, chloroform and tetrahydrofuran.

[0014] Preferably, in step (2), the stirring and immersion temperature is 10-35°C; the stirring and immersion time is 12-36 hours, preferably 24-30 hours.

[0015] Beneficial Effects (1) The present invention first adds an organic ligand to a solvent to obtain a mixed solution, and after the organic ligand is completely dissolved, a metallic titanium source is added, and the solution is transferred to a high-pressure reactor for high-temperature reaction. Due to the effects of high temperature and high pressure, titanium ions can effectively coordinate with the organic ligand, which is beneficial to the formation of MIL-125 material. The reaction liquid is washed, separated and dried to obtain a MIL-125 material with a high specific surface area, and then the MIL-125 material and PMA are added to the solvent for impregnation, so that PMA can be effectively loaded into MIL-125; (2) The present invention adopts a two-step synthesis method to prepare the PMA@MIL-125 composite photocatalyst material, which has the advantages of simplicity, low cost, good repeatability, high yield, and controllable process. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The crystal structure XRD diagrams of MIL-125, PMA and PMA@MIL-125 in Example 1; Figure 2 The morphology and structure SEM images of MIL-125 and PMA@MIL-125 in Example 1; Figure 3 TEM images of the morphology and structure of MIL-125 and PMA@MIL-125 in Example 1; Figure 4 The nitrogen adsorption-desorption curves of MIL-125 and PMA@MIL-125 in Example 1; Figure 5 IR spectra of MIL-125, PMA and PMA@MIL-125 in Example 1; Figure 6 Thermogravimetric analysis curves of MIL-125, PMA and PMA@MIL-125 in Example 1; Figure 7 Schematic diagram of the degradation curves of mobile phase acetone in evaluation experiment 2, evaluation experiment 3, comparative evaluation 3, comparative evaluation 4, and comparative evaluation 5. DETAILED DESCRIPTION

[0017] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0018] First, the present invention provides a novel polyoxometalate-loaded metal organic framework composite photocatalytic material for air purification, wherein the composite photocatalytic material for air purification comprises: a MIL-125MOF material, and a phosphomolybdic acid (PMA) material encapsulated and loaded in the pores of the MIL-125MOF material.

[0019] Among them, the phosphomolybdic acid (PMA, H3PMo 12 O 40 ) is a polyoxometalate cluster, which is cheap, has strong electron storage capacity and can be used as a reservoir for photoelectrons. However, PMA is easy to agglomerate and is prone to uneven distribution on the carrier. In the present invention, the pore size of the MIL-125 material (approximately ) and PMA molecular size (ca. ). The ordered pore structure in the MIL-125 material ensures the uniform distribution of PMA, which can effectively prevent the aggregation and precipitation of PMA. Moreover, the energy level matching between PMA and MIL-125 is high, which is conducive to the transfer and separation of charges, thereby reducing the recombination rate of photogenerated carriers in the MIL-125 material and increasing the number of photogenerated carriers in the MIL-125 material. In addition, MIL-125 has a high specific surface area and can effectively capture oxygen-containing VOCs molecules in the gas phase. Ultimately, the synergistic effect between the two can effectively improve the photocatalytic degradation efficiency of oxygen-containing VOCs.

[0020] Furthermore, the appropriate pore size and ordered pore structure of MIL-125 material ensure the uniform distribution of PMA. The interaction between PMA and MIL-125 can effectively prevent the aggregation of PMA. MIL-125 has a high specific surface area, closed channels, and adjustable hydrophobic and hydrophilic microenvironments, which allow the exposure of active sites for catalysis and facilitate the rapid diffusion of reactants and products. The light-harvesting ability of MIL-125, good interaction, and electron transfer between MIL-125 and PMA can synergistically improve the photocatalytic performance.

[0021] In some embodiments, based on the total mass of the composite photocatalytic material for air purification being 100%, the mass proportion of the PMA material can be 30-50%, and the mass proportion of the MIL-125MOF material can be 50-70%. By controlling the contents of the two within an appropriate range, it is possible to avoid excessive PMA occupying the pore position and hindering the diffusion of pollutant molecules, and it is also possible to avoid too little PMA, resulting in weak photocatalytic activity.

[0022] In some embodiments, the average pore size of the MIL-125MOF material may be 1-5 nm.

[0023] In some embodiments, the particle size of the composite photocatalytic material for air purification may be in the range of 400-1000 nm.

[0024] In some embodiments, the specific surface area of ​​the composite photocatalytic material for air purification can be 800-1500m 2 / g.

[0025] The following is an exemplary description of the preparation method of the composite photocatalytic material for air purification provided by the present invention. The preparation method may include the following steps: (1) dissolving an organic ligand in a first solvent, adding a metallic titanium source to obtain a mixed solution, and subjecting the solution to high-temperature heating reaction to obtain the MIL-125MOF material; (2) The PMA material and the MIL-125MOF material are stirred and immersed in a second solvent to obtain the composite photocatalytic material for air purification.

[0026] In some embodiments, in step (1), the organic ligand may include at least one of terephthalic acid, 2-aminoterephthalic acid, 2-hydroxyterephthalic acid, 2-nitroterephthalic acid, 2,5-diaminoterephthalic acid, 2,5-dihydroxyterephthalic acid, tetrafluoroterephthalic acid, isophthalic acid, phthalic acid, trimesic acid, trimellitic acid, biphenyl trimesic acid, 2,5-dicarboxypyridine, biphenyl dicarboxylic acid, and bipyridine dicarboxylic acid; preferably terephthalic acid or 2-aminoterephthalic acid.

[0027] In some embodiments, in step (1), the first solvent may include at least one of methanol, ethanol, acetic acid, deionized water, dimethylformamide (DMF), dimethyl sulfoxide (DMSO), 1,3-dimethyl-2-imidazolidinone (DMI), diethylene glycol monomethyl ether (DEM), and tetrahydrofuran (THF); preferably, it is a mixture of methanol, acetic acid, and dimethylformamide (DMF).

[0028] In some embodiments, in step (1), the metal titanium source may include at least one of tetrabutyl titanate, titanium isobutoxide, titanium tetraisopropoxide, tetraethyl titanate, n-propyl titanate, tetrahydrofuran titanium chloride, isopropyl titanate triisostearate, triisopropoxy titanium chloride, and titanium tert-butoxide; preferably at least one of titanium tetraisopropoxide and tetraethyl titanate.

[0029] In some embodiments, in step (1), the molar ratio of the metal titanium source and the organic ligand may be (0.2-2): 1, preferably (0.5-0.8): 1. By controlling the molar ratio of the two within this range, the metal titanium source and the organic ligand can be effectively utilized to avoid the waste of raw materials.

[0030] In some embodiments, in step (1), the temperature of the high temperature heating reaction can be 120-180°C, preferably 140-170°C; the time of the high temperature heating reaction can be 12-48 hours, preferably 24-36 hours. If the temperature is too low or the reaction time is too short, a highly crystalline material cannot be obtained.

[0031] In some embodiments, in step (2), the second solvent is a medium polar solvent; preferably at least one of methanol, ethanol, acetonitrile, chloroform, and tetrahydrofuran (THF).

[0032] Among them, phosphomolybdic acid PMA shows strong acidity in the strong polar solvent water, which will destroy the structure of MIL-125 during the preparation of the composite material and weaken the photocatalytic ability of the composite material. On the other hand, PMA is difficult to ionize in low-polarity solutions such as n-hexane, benzene, toluene or xylene, so that the loading amount of PMA in the preparation process of the composite material is low, and the photocatalytic effect of MIL-125 is weak. Therefore, the present invention creatively uses a medium polar solvent for stirring and impregnation to synthesize a composite photocatalytic material, which will not destroy the structure of MIL-125 and can ensure a suitable PMA loading amount.

[0033] In some embodiments, in step (2), the temperature of the stirring and dipping can be 10-35° C.; the time of the stirring and dipping can be 12-36 hours, preferably 24-30 hours.

[0034] In the preparation method provided by the present invention, a certain amount of organic ligand is first added to a solvent to obtain a mixed solution, and a metal titanium source is added after the organic ligand is completely dissolved, and the above solution is transferred to a high-pressure reactor for high-temperature reaction. Due to the effect of high temperature and high pressure, titanium ions can effectively coordinate with organic ligands, which is conducive to the formation of MIL-125 materials. The reaction liquid is washed, separated and dried to obtain a MIL-125 material with a high specific surface area. If the temperature is too low or the reaction time is too short, a high crystalline material cannot be obtained. In addition, phosphomolybdic acid PMA shows strong acidity in strong polar solvents such as water, which will destroy the structure of MIL-125 and weaken the photocatalytic ability of its composite material. On the other hand, PMA is difficult to ionize in low-polarity solutions such as n-hexane, benzene, toluene or xylene, and the loading amount is low, and the photocatalytic effect of MIL-125 is weakly improved. Therefore, MIL-125 and PMA are added to a certain amount of medium polar solvents for immersion, and PMA can be effectively loaded into MIL-125. The present invention adopts a two-step synthesis method to prepare the PMA@MIL-125 composite photocatalyst material, which has the advantages of simplicity, low cost, good repeatability, high yield, controllable process, etc.

[0035] The composite photocatalytic material for air purification obtained by the preparation method provided by the invention is suitable for photocatalytic degradation of oxygen-containing volatile organic compounds including acetone and acetaldehyde.

[0036] In some embodiments, under the premise of acetone concentration of 25-500 ppm and flow rate of 10-100 mL / min, the photocatalytic degradation efficiency can reach 33-80% under the condition of 250-500 W xenon lamp as light source.

[0037] In some embodiments, under the premise of acetaldehyde concentration of 25-500 ppm and flow rate of 10-100 mL / min, the photocatalytic degradation efficiency can reach 18-86% under the condition of 250-500 W xenon lamp as light source.

[0038] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values ​​​​exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0039] Unless otherwise specified, the present invention selects acetone and acetaldehyde as target pollutants to evaluate the performance of the obtained photocatalyst. Acetone and acetaldehyde are two typical oxygen-containing VOCs as target pollutant gases, which have small molecular sizes and contain C=O functional groups. They are mainly derived from industries such as plastic production, pharmaceuticals, and spray painting.

[0040] Example 1

[0041] The preparation method of the composite photocatalytic material for air purification provided in this embodiment comprises the following steps: (1) Adding the organic ligand 2-aminoterephthalic acid (3.1 mmol, 0.56 g) to a mixed solution of DMF / methanol / acetic acid (36 mL / 4 mL / 2.1 mL) and ultrasonically stirring for 30 minutes to allow the organic ligand to be uniformly dissolved in the solution, then adding titanium tetraisopropoxide (2 mmol, 0.6 mL) to obtain a mixed solution, and quickly transferring the mixed solution to a polytetrafluoroethylene reactor, the reaction temperature and time are 150 ° C and 24 hours respectively; after the reaction is completed, let it cool naturally to room temperature, wash it with DMF and methanol respectively, centrifuge it 3 times, vacuum dry it and grind it to obtain MIL-125MOF powder material; (2) 100 mg of PMA was dissolved in 5 mL of methanol solution and stirred evenly. Then, 100 mg of the above-mentioned MIL-125MOF powder material was added while stirring. After stirring for 24 hours, the mixture was washed with methanol and centrifuged three times. PMA (H3PMo) was obtained by vacuum drying. 12 O 40 ) loaded with MIL-125 material and marked as PMA@MIL-125.

[0042] The crystal structures of MIL-125, PMA and PMA@MIL-125 in Example 1 were characterized by XRD. Figure 1 It can be seen that PMA@MIL-125 has both the diffraction peaks of MIL-125 and the diffraction peaks of PMA, indicating that PMA is successfully loaded into MIL-125.

[0043] The morphology and structure of MIL-125 and PMA@MIL-125 in Example 1 were examined by SEM. Figure 2 It can be seen that the loading of PMA does not significantly change the morphology of MIL-125, showing a polyhedral structure with a grain size in the range of 400-1000nm.

[0044] Figure 3 TEM images of the morphology and structure of MIL-125 and PMA@MIL-125 in Example 1. Figure 3 It can also be seen that the loading of PMA does not significantly change the morphology of MIL-125, showing a polyhedral structure, and the photocatalyst particles are approximately 500nm.

[0045] The specific surface areas of MIL-125 and PMA@MIL-125 in Example 1 were tested by nitrogen adsorption-desorption experiments to examine the effect of PMA loading on their surface areas. Figure 4 It can be seen that MIL-125 and PMA@MIL-125 have a sharp absorption at P / P0<0.1, which indicates that there are a large number of microporous structures inside MIL-125 and PMA@MIL-125. This microporous structure originates from the intrinsic pores in MIL-125, which is conducive to the capture of gas phase pollutant molecules. In addition, the specific surface areas of MIL-125 and PMA@MIL-125 are 1345m 2 / g and 901m 2 / g, and this decrease in specific surface area also indicates that PMA was successfully loaded into MIL-125, resulting in the blocking of some intrinsic micropores in MIL-125.

[0046] The MIL-125, PMA and PMA@MIL-125 in Example 1 were further characterized by infrared spectroscopy. Figure 5 It can be seen that compared with MIL-125, PMA@MIL-125 has three new infrared peak signals, with wave numbers at 1064, 964 and 800 cm -1 , of which 1064cm -1 Corresponding to the asymmetric stretching vibration of the PO bond in the PMA molecule, 964 cm -1 Corresponding to the asymmetric stretching vibration of the Mo=O bond in the PMA molecule, 800cm -1This corresponds to the asymmetric stretching vibration of the Mo-O bond in the PMA molecule, indicating that the PMA molecule is successfully loaded in PMA@MIL-125 and its structure still maintains the Keggin configuration. In addition, compared with the Mo-O bond in PMA (wave number at 784 cm -1 ), the Mo-O bond in PMA@MIL-125 is obviously blue-shifted (wave number at 800 cm -1 ), which indicates that the PMA molecules in PMA@MIL-125 will interact strongly with the MIL-125 molecules.

[0047] The stability of the catalyst was evaluated by thermogravimetric analysis. Figure 6 It can be seen that the PMA molecule will have an obvious mass loss at 150°C, which corresponds to the decomposition of the PMA molecule to form MoO3; the mass loss in MIL-125 at less than 250°C corresponds to the removal of solvent molecules inside the material; the final residual mass in PMA@MIL-125 is higher than the residual mass of MIL-125, which also indicates that the PMA molecule is successfully loaded in MIL-125.

[0048] Example 2

[0049] The preparation method of the composite photocatalytic material for air purification provided in this embodiment refers to that in Example 1, the main difference is that: In step (1), the organic ligand terephthalic acid (9 mmol, 1.5 g) was added to a mixed solution of DMF / methanol 36 mL / 4 mL and ultrasonically stirred for 60 minutes; the temperature and time of the high temperature heating reaction were 160° C. and 48 hours, respectively, and the obtained white MIL-125MOF powder material was marked as MIL-125-N0; In step (2), the composite photocatalytic material for air purification finally prepared is marked as PMA@MIL-125-N0.

[0050] Example 3

[0051] The preparation method of the composite photocatalytic material for air purification provided in this embodiment refers to that in Example 1, the main difference is that: In step (1), organic ligand terephthalic acid (3 mmol, 0.5 g) and 2-aminoterephthalic acid (3 mmol, 0.54 g) were added to 40 mL DMF solution and ultrasonically stirred for 60 minutes; the high temperature heating reaction time was 36 hours, and the obtained white MIL-125MOF powder material was marked as MIL-125-N50; In step (2), the composite photocatalytic material for air purification finally prepared is marked as PMA@MIL-125-N50.

[0052] Comparative Example 1

[0053] The preparation method of the catalytic material provided in this comparative example 1 refers to that in Example 1, the main difference is that: In step (2), the second solvent is replaced with a highly polar solvent, deionized water, and the catalytic material finally prepared is labeled as PMA@MIL-125-H.

[0054] Comparative Example 2

[0055] The preparation method of the catalytic material provided in this comparative example refers to that in Example 1, the main difference is that: In step (2), the solvent is replaced with a low-polarity solvent, toluene, and the catalytic material finally prepared is labeled as PMA@MIL-125-B.

[0056] The performance of the catalyst provided by the present invention is evaluated below:

[0057] Evaluation Experiment 1

[0058] Take 20 mg of the PMA@MIL-125 powder in Example 1, add it to 2 mL of ethanol solution, and ultrasonically disperse it for 5 minutes to make it highly dispersed and uniform; apply it to a 7.5 cm×15 cm transparent glass sheet to form a coating, and then put the glass sheet into an oven and dry it at 80°C for 30 minutes to completely remove the residual ethanol solvent to form a dry coating; then put the glass plate into a 120 mL mobile phase reaction chamber to perform a photocatalytic degradation of acetone test; the acetone concentration is selected as 400 ppm and 25 ppm, and the flow rate is selected as 20 mL / min; gas chromatography is used to detect the real-time gas concentration, and the adsorption amount of the photocatalyst is detected under dark conditions.

[0059] Evaluation Experiment 2

[0060] Take 20 mg of the PMA@MIL-125 powder in Example 1, add it to 2 mL of ethanol solution, and ultrasonically disperse it for 5 minutes to make it highly dispersed and uniform; apply it to a 7.5 cm×15 cm transparent glass sheet to form a coating, and then put the glass sheet into an oven and dry it at 80°C for 30 minutes to completely remove the residual ethanol solvent to form a dry coating; then put the glass plate into a 120 mL mobile phase reaction chamber to perform a photocatalytic degradation of acetone test; the acetone concentration is selected to be 400 ppm and the flow rate is selected to be 20 mL / min; use gas chromatography to detect the real-time gas concentration, and a 500 W xenon lamp is used as the light source; when the adsorption equilibrium is reached under dark conditions, start the photodegradation experiment.

[0061] Evaluation Experiment 3

[0062] Refer to Evaluation Experiment 2, the main difference is: the acetone concentration is changed to 25ppm.

[0063] Evaluation Experiment 4

[0064] Refer to Evaluation Experiment 2, the main difference is: PMA@MIL-125 is replaced by PMA@MIL-125-N0.

[0065] Evaluation Experiment 5

[0066] Referring to evaluation experiment 2, the main differences are: PMA@MIL-125 was replaced by PMA@MIL-125-N0, and the acetone concentration was changed to 25 ppm.

[0067] Evaluation Experiment 6

[0068] Take 20 mg of the PMA@MIL-125 powder in Example 1, add it to 2 mL of ethanol solution, and ultrasonically disperse it for 5 minutes to make it highly dispersed and uniform; apply it to a 7.5 cm×15 cm transparent glass sheet to form a coating, and then put the glass sheet into an oven and dry it at 80°C for 30 minutes to completely remove the residual ethanol solvent to form a dry coating; then put the glass plate into a 120 mL mobile phase reaction chamber to perform a photocatalytic degradation of acetone test; the acetaldehyde concentration is selected to be 500 ppm, and the flow rate is selected to be 20 mL / min; use gas chromatography to detect the real-time gas concentration, and a 500 W xenon lamp is used as the light source; start the illumination experiment when the adsorption equilibrium is reached under dark conditions.

[0069] Comparative evaluation 1

[0070] Refer to evaluation experiment 1, the main difference is that PMA@MIL-125 powder is replaced by MIL-125.

[0071] Comparative evaluation 2

[0072] Refer to evaluation experiment 1, the main difference is that PMA@MIL-125 powder is replaced by PMA material.

[0073] Comparative evaluation 3

[0074] Refer to Evaluation Experiment 2, the main difference is: PMA@MIL-125 powder is replaced by MIL-125.

[0075] Comparative evaluation 4

[0076] Refer to Evaluation Experiment 2, the main differences are: PMA@MIL-125 powder was replaced by MIL-125, and the acetone concentration was changed to 25ppm.

[0077] Comparative evaluation 5

[0078] Refer to evaluation experiment 2, the main difference is: PMA@MIL-125 powder is replaced by PMA material.

[0079] Comparative evaluation 6

[0080] Refer to evaluation experiment 2, the main difference is that the PMA@MIL-125 powder is replaced by MIL-125-N0 material.

[0081] Comparative evaluation 7

[0082] Refer to evaluation experiment 2, the main difference is that the PMA@MIL-125 powder is replaced by MIL-125-N50 material.

[0083] Comparative evaluation 8

[0084] Refer to evaluation experiment 2, the main differences are: PMA@MIL-125 powder is replaced by MIL-125-N50 material, and the acetone concentration is changed to 25ppm.

[0085] Comparative evaluation 9

[0086] Refer to Evaluation Experiment 6, the main difference is that the PMA@MIL-125 powder is replaced by MIL-125 material.

[0087] Comparative evaluation 10

[0088] Refer to Evaluation Experiment 6, the main difference is that the PMA@MIL-125 powder is replaced by PMA material.

[0089] Comparative evaluation 11

[0090] Referring to evaluation experiment 6, the main difference is that PMA@MIL-125 powder is replaced by PMA@MIL-125-B material.

[0091] Comparative evaluation 12

[0092] Referring to evaluation experiment 6, the main difference is that the PMA@MIL-125 powder is replaced by PMA@MIL-125-H material.

[0093] By calculating the adsorption results of 400ppm mobile phase acetone in evaluation experiment 1, comparative evaluation 1, and comparative evaluation 2, it can be found that the high specific surface area of ​​MIL-125 gives the material excellent acetone adsorption performance, and its use as a substrate is conducive to the subsequent photocatalytic degradation of acetone molecules. The specific adsorption results are shown in Table 1: Table 1 Adsorption data of acetone gas in evaluation experiment 1, comparative evaluation 1 and comparative evaluation 2 Serial number Adsorption time (minutes) Adsorption capacity (mmol / g) Comparative evaluation 1 150 minutes 0.351 Evaluation Experiment 1 150 minutes 0.278 Comparative evaluation 2 150 minutes 0.236

[0094] Through the test results of acetone photodegradation of evaluation experiment 2, evaluation experiment 3, evaluation experiment 4, evaluation experiment 5, evaluation experiment 6, comparative evaluation 3, comparative evaluation 4, comparative evaluation 5, comparative evaluation 7, comparative evaluation 8, comparative evaluation 9, and comparative evaluation 10, it can be found that the loading of PMA can improve the catalytic performance of MIL-125 materials regardless of whether it is at high concentration (400ppm) acetone or low concentration (25ppm) acetone. Through the test results of evaluation experiment 6 and comparative evaluation 9, it can be found that the loading of PMA also has a very obvious promoting effect on the photocatalytic degradation of acetaldehyde. In addition, PMA alone does not have photocatalytic properties, which shows that the role of PMA is to increase the photoelectron storage capacity of MIL-125 materials. The specific degradation efficiency is shown in Table 2: Table 2 Evaluation experiment 2, evaluation experiment 3, evaluation experiment 4, evaluation experiment 5, evaluation experiment 6, comparative evaluation 3, comparative evaluation 4, comparative evaluation 5, comparative evaluation 6, comparative evaluation 8, comparative evaluation 9, comparative evaluation 10, comparative evaluation 11, comparative evaluation 12 Photocatalytic degradation efficiency

[0095] Figure 7 Schematic diagram of the degradation curves of mobile phase acetone in evaluation experiment 2, evaluation experiment 3, comparative evaluation 3, comparative evaluation 4, and comparative evaluation 5.

[0096] The PMA-loaded MIL-125 composite photocatalyst material provided by the present invention has readily available raw materials, a simple preparation process, and low requirements for experimental conditions and equipment. The PMA@MIL-125 composite photocatalyst material obtained in the embodiment combines the characteristics of the high specific surface area of ​​the MIL-125 material, and has excellent adsorption capacity for oxygen-containing VOCs, and combines the characteristics of the PMA material for storing charges, and can effectively degrade acetone and acetaldehyde gases in a flow system, and has high photocatalytic degradation performance. The material has broad application prospects in the field of air purification.

[0097] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A composite photocatalytic material for air purification, characterized in that: The composite photocatalytic material for air purification comprises: a MIL-125MOF material with a high specific surface area, and a phosphomolybdic acid PMA material encapsulated and loaded in the pores of the MIL-125MOF material; Wherein, taking the total mass of the composite photocatalytic material for air purification as 100%, the mass of the PMA material accounts for 30-50%, and the mass of the MIL-125MOF material accounts for 50-70%.

2. The composite photocatalytic material for air purification according to claim 1, characterized in that: The average pore size of the MIL-125MOF material is 1-5 nm.

3. The composite photocatalytic material for air purification according to claim 1 or 2, characterized in that: The crystal grain size of the composite photocatalytic material for air purification ranges from 400 to 1000 nm.

4. The composite photocatalytic material for air purification according to any one of claims 1 to 3, characterized in that: The specific surface area of ​​the composite photocatalytic material for air purification is 800-1500m 2 / g.

5. A method for preparing a composite photocatalytic material for air purification according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) dissolving an organic ligand in a first solvent, adding a metallic titanium source to obtain a mixed solution, and subjecting the solution to high-temperature heating reaction to obtain the MIL-125MOF material; (2) The PMA material and the MIL-125MOF material are stirred and immersed in a second solvent to obtain the composite photocatalytic material for air purification.

6. The preparation method according to claim 5, characterized in that: In step (1), the organic ligand comprises at least one of terephthalic acid, 2-aminoterephthalic acid, 2-hydroxyterephthalic acid, 2-nitroterephthalic acid, 2,5-diaminoterephthalic acid, 2,5-dihydroxyterephthalic acid, tetrafluoroterephthalic acid, isophthalic acid, phthalic acid, trimesic acid, trimellitic acid, biphenyl trimesic acid, 2,5-dicarboxypyridine, biphenyl dicarboxylic acid, and bipyridine dicarboxylic acid; The metal titanium source includes at least one of tetrabutyl titanate, titanium isobutoxide, titanium tetraisopropoxide, tetraethyl titanate, n-propyl titanate, tetrahydrofuran titanium chloride, isopropyl titanate triisostearate, triisopropoxy titanium chloride, and titanium tert-butoxide.

7. The preparation method according to claim 5 or 6, characterized in that: In step (1), the molar ratio of the metallic titanium source to the organic ligand is (0.2-2):1, preferably (0.5-0.8):

1.

8. The preparation method according to any one of claims 5 to 7, characterized in that: In step (1), the temperature of the high temperature heating reaction is 120-180° C., preferably 140-170° C.; the time of the high temperature heating reaction is 12-48 hours, preferably 24-36 hours.

9. The preparation method according to any one of claims 5 to 8, characterized in that: In step (2), the second solvent is a medium polar solvent; preferably at least one of methanol, ethanol, acetonitrile, chloroform and tetrahydrofuran.

10. The preparation method according to any one of claims 5 to 9, characterized in that: In step (2), the stirring and dipping temperature is 10-35° C.; the stirring and dipping time is 12-36 hours, preferably 24-30 hours.